Voltammetric determination of persulfate anions using an electrode modified with a Prussian blue film - de Oliveira, M. F.; Mortimer, R. J.; Stradiotto, Nelson Ramos [UNESP] (Elsevier B.V., 2000)
Prussian blue [PB, iron(III) hexacyanoferrate(II)] films are effective for the electrocatalysis of the persulfate (peroxodisulfate)/sulfate redox system. This has been exploited in the voltammetric determination of persulfate anions using a PB-modified platinum disc electrode. A linear correlation between electrocatalytic current and persulfate concentration was found for the range 5 x 10(-5) to 3 x 10(-3) mol dm(-3), using 0.100 mol dm(-3) potassium chloride as supporting electrolyte at pH 4. This analytical method has the advantages of speed and ease of operation in relation to traditional titrimetric methods for persulfate determination. The applicability of the method to the determination of persulfate in a commercial hair bleaching 'booster' product is demonstrated. (C) 2000 Elsevier B.V. B.V. All rights reserved.
Keywords: modified electrodes; sensors; Prussian blue; persulfate